Formulation of Female Liquid Soap from Leaf Tanjung Extract (Mimusp elengy L) and its effectiveness on Growth of Candida albicans - Sulfiyana H. Ambo Lau; Nurul Izza AR; Muh Riswan (Jurnal Farmasi Sandi Karsa, 2021)
This study aims to determine the formulation of Liquid Soap for Women from Tanjung Leaf Extract (Mimusops elengi L) and its effectiveness on the growth of Candida albicans and the most effective concentration. The type of research used is experimental research which is a laboratory study using a simple experimental design, namely the effectiveness of antifungal preparations for female liquid soap extracts from tanjung leaves (Mimusops elengi L) against Candida albicans. This research was conducted in September 2021 at the Laboratory of Pharmaceutical Biology, Pharmaceutical Technology and Pharmacognosy-Phytochemistry of Pharmacy, Sandi Karsa Polytechnic. The results of statistical analysis using the completely randomized design method (ANOVA) showed that giving a negative control of the preparation of female liquid soap with tanjung leaf extract and Resik V liquid soap as a comparison gave a significantly different inhibition zone against Candida albicans, where the inhibition zone showed that the F value of the zone inhibition against Candida albicans was greater than Ftable at the level of 0.05 (3.48) and Ftable at the level of 0.01 (5.99), it can be concluded that the preparation of female cleansing liquid soap from tanjung leaf extract (Mimusops elengi L) concentration 1 % w/v, 3% w/v, and 5% w/v can inhibit Candida albicans.